Punching shear failure of concrete-filled steel tubular CHS connections. (September 2016) - Xu, Fei; Chen, Ju; Jin, Wei-liang
Abstract: Based on the experimental investigation and numerical simulation, the punching shear failure mode of concrete-filled steel tubular CHS (circular hollow section) connections in axial tension was investigated. A finite element model was established using ABAQUS and verified against test results. It is shown that the developed model predicts the ultimate strengths and failure modes of test specimens well. Material properties, sizes of weld and contact interaction between concrete and steel were considered in the developed finite element model. The modified Mohr-Coulomb criterion for ductile fracture was used to define fracture criterion of the steel tube. Distribution of shear stress on the punching shear face was examined and a general equation describing stress distribution was proposed. An equation for equivalent thickness of punching shear failure face was also proposed. Parametric study was performed to determine the parameters in the proposed equations. Finally, design equations for ultimate strengths of concrete-filled steel tubular CHS connections failed in chord punching shear failure were proposed. It is shown that the design predictions agree with the finite element analysis results well. Highlights: The punching shear failure mode of concrete-filled steel tubular CHS connections in axial tension was investigated. The modified Mohr-Coulomb criterion for ductile fracture was used to define the fracture criterion of the steel tube. Distribution of shear stress on the punching shear face was examined and an equation was proposed. Design equations for concrete-filled steel tubular CHS connections failed in the chord punching shear failure were proposed.